(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The rapid depletion of non-renewable fossil fuels such as coal, petroleum, and gas has led to a global energy crisis and environmental pollution. Hydrogen and biobutanol have emerged as vital renewable energy sources due to their cleanliness and high energy potential (122 kj/g). The production of renewable energy from these sources involves the utilization of nanoparticles in conjunction with microorganisms from the Clostridial bacteria family. The active sites of hydrogenase metal atoms, namely NiFe, FeFe, and Fe-hydrogenase, play a significant role in this process. Iron (Fe) metals particularly influence hydrogen production, as they enhance the activity of the hydrogenase enzyme. Fe is an essential component of cytochromes found in anaerobic microbes. Consequently, introducing Fe-based nanoparticles is assumed to promote microbial cell growth and hydrogenase activity. Various factors, such as nanoparticle size, concentration, operational conditions, operational mode, and substrate, impact the production of biohydrogen and biobutanol. Furthermore, a protein sequence analysis reveals the presence of a multi-active site for amylase activity in Clostridium. This discovery suggests that this enzyme can translate and augment biofuel production rates. By exploring and harnessing these avenues, the world can advance toward a more sustainable future by capitalizing on the potential of hydrogen and biobutanol as renewable energy sources while mitigating the negative consequences of the depletion of non-renewable fossil fuels.